EFEKTIVITAS BUAH KURMA TERHADAP KADAR HEMOGLOBIN REMAJA PUTRI - Rohmah, Hajar Nur Fathur; Musmundiroh, Musmundiroh; Marliyanti, Ineu (Jurnal Ilmiah Maternal, 2025)
The main health problem that arises in adolescent girls is the lack of nutritional intake as a cause of iron deficiency anemia which results in the nutritional status of adolescents. The government has launched a TTD (Iron Supplement Tablet) program for adolescents, but there are obstacles, including the bitter taste and unpleasant aroma for consumption, so the program does not run well. For this reason, alternatives are needed by consuming other foods. One alternative food ingredient that can be eaten to treat iron deficiency anemia is dates, which have an iron content of 1.5 mg per fruit. Dates also have a good taste and are liked by all age groups. Giving dates to hemoglobin levels shows that giving dates has quite an effect on increasing hemoglobin levels. The advantages of dates themselves can be consumed directly without being processed first. A preliminary study of 180 female students showed that 23% of SMKN 1 Setu had anemia. The purpose of this study was to determine the effectiveness of giving dates to hemoglobin levels. This type of research is a quasi experiment. The population in this study were 536 female students of SMKN 1 Setu. The sampling technique used purposive sampling with a sample size of 82 people. Data analysis in this study used paired t-Test. The results of the study obtained a p-value of 0.000. It can be concluded that there is an effect of giving dates on increasing hemoglobin levels in female students at SMKN 1 Setu.